Environmental impact assessment of milk packaging in Canada. (20th November 2021) - Sun, Jon-Paul; Calahoo, Courtney; Brown, Colby; White, Mary Anne
Abstract: The present study reports quantitative environmental impact assessments for types of milk packaging presently available in Canada: 4 L packages of pillow pouches ('milk bags', containing three 1.33 L pillow pouches), 4 L and 2 L high-density polyethylene (HDPE) jugs, and 2 L and 1 L screw-cap gable-top liquid packaging board (LPB) cartons. The purpose of the investigation was to inform consumers and other stakeholders of the relative environmental impacts of the milk packaging choice. The simplified life cycle assessment consisted of quantification of the energy consumption, global warming potential (quantified as CO2 equivalent emissions) and water consumption associated with the functional unit of milk use for one average Canadian household of 2.6 people for one year (163.4 L). The steps considered included primary production and processing of the materials, and delivery to the city (Toronto, Ontario, Canada or Halifax, Nova Scotia, Canada) where they would be filled with milk and the milk would be consumed. Four different end-of-life scenarios for each of the five different types of packaging were considered: 100% recycled; 100% incinerated (where the energy of incineration is captured with 100% efficiency); 100% landfill (CO2 not released); and actual recycling rate at that location, with remainder in landfill. The embodied energy, GHG emissions and water consumption factors all indicate that pillow pouches have the lowest impact of the investigated types of packaging for milk in Canada, regardless of location. The main reason for the significantly lower impact of the pouches is their lower mass per functional unit compared with jugs and cartons. Pillow pouches are better across all impact categories than the alternatives, even if the pillow pouches are disposed in the landfill or incinerated and the alternatives are fully recycled. Graphical abstract: Image 1